Euthanasia and the Assessment of Patients' Autonomy Rights in the Indonesian Criminal Code - Fanny Tanuwijaya (University of Jember, 2020)
This study aims to analyze and clarify the application of criminal law principles in cases of euthanasia. The concept of euthanasia is a new thought in criminal law that arises because of humans' desire to determine life's direction. The realization of life's ownership of oneself gives birth to the thought that one can hasten one's death. The conception of self-determination in euthanasia is by realizing the right to autonomy, which is an essential principle in medical law. However, the manifestation of euthanasia as the fulfillment of autonomy has a conflict with criminal law, especially in Indonesia. In Indonesia, the conflict of norms on euthanasia and the provisions of criminal law can be seen in the legislative product, namely the Criminal Code (KUHP), which clearly reflects euthanasia prohibition. A study of euthanasia in criminal law principles shows that health regulation, especially regarding euthanasia, needs to pay attention to the right to patient autonomy as its main principle. The conflict over the right to autonomy and Indonesian criminal law creates a conflict of norms that further tests euthanasia's legality in Indonesia. KEYWORDS: Indonesian Criminal Code. Patient's Autonomy, Religious Values.